Explaining international differences in genetically modified food labeling policies - Gruère, Guillaume P.; Carter, Colin A.; Farzin, Y. Hossein (Wiley, 2009)
Many countries have adopted labeling policies for genetically modified (GM) food, and the regulations vary considerably across countries. We evaluate the importance of political‐economic factors implicit in the choice of GM food labeling regulations. Using an analytical model, we show that production and trade‐related interests play a prominent role in labeling decision‐making. This conclusion is validated by an empirical analysis of GM food labeling policy choices. We find that countries producing GM crops are more likely to have less stringent labeling policies. Food and feed exporters to the European Union (EU) and Japan are more likely to have adopted stricter labeling policies. Labeling regulations in Asia and Europe are similar to those of Japan and the EU. Countries with no labeling policies are less developed, with important rural sectors and are more likely to have ratified the Cartagena Protocol on Biosafety.